Management of Delirium in Adult Critically ill Patients: An Overview - Hoan Linh Banh (Frontiers Media S.A., 2012)
Delirium is a common manifestation of acute, reversible, brain dysfunction in critically ill patients. It is associated with increased morbidity and mortality in the intensive care unit (ICU). Detection and prevention of risk factors for delirium is critical. Daily assessment for delirium should be part of the treatment strategies. Although, non-pharmacologic treatment have been successful, often, pharmacologic intervention is necessary. Currently, there are no approved medications indicated for the treatment of ICU delirium. The objective of this review article is to provide a comprehensive overview of non-pharmacologic and pharmacologic options for the treatment of ICU delirium. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.